Neonectria fuckeliana infection of Pinus radiata nursery stock - Dick, M.A.; Power, M.W.P.; Carlson, C.A. (New Zealand Plant Protection, 2011)
Nectria flute canker is a disease of Pinus radiata stems caused by Neonectria fuckeliana The fungus is not known in the North Island leading to concern that it may be transported north via asymptomatically colonised nursery stock Wounded P radiata seedlings and cuttings were exposed to natural inoculum from an adjacent infected forest and half were artificially inoculated No disease symptoms were recorded throughout the trial Neonectria fuckeliana was reisolated from 24 and 7 of inoculated seedlings and cuttings respectively 3 months after inoculation and at 12 months from 35 of the remaining inoculated seedlings only Neonectria fuckeliana was not isolated from uninoculated seedlings or cuttings exposed to natural inoculum These results indicate that nursery plants have little capability of retaining N fuckeliana within the tissue even when directly inoculated Nursery stock is therefore unlikely to be a pathway for transport of the fungus